Efektivitas Penyelesaian Sengketa Kontrak Konstruksi di Indonesia dalam Analisis Hukum Implementasi dan Tantangan Proyek Infrastruktur - Hapit Sugandi; Samian Samian; Adi Saputro (Publikasi Indonesia, 2025)
This study analyzes the effectiveness of the construction contract dispute resolution mechanism in the context of accelerating Indonesia's national infrastructure development. Through a normative juridical approach with the literature study method, the research examines the coherence of the legal framework and its implementation in the settlement of construction disputes. The results of the analysis revealed that although Indonesia already has a comprehensive legal instrument, there is a significant gap between regulations and practices in the field. The gap is mainly caused by three main factors: the complexity of modern construction contracts involving multiple stakeholders, the limited understanding of the parties to the legal aspects of construction, and structural obstacles in the execution of dispute resolution decisions. Based on these findings, the study recommends three optimization strategies: improving the legal framework through regulatory harmonization, strengthening the institutional capacity of dispute resolution, and developing alternative dispute resolution mechanisms that are more responsive to the characteristics of the construction industry. The implementation of this recommendation is expected to increase the effectiveness of construction dispute resolution and support the sustainability of national infrastructure development